Prevalence of surgical patients at risk of obstructive sleep apnea (OSA) at preoperative Anaesthesia Clinic in Hospital Serdang - Liyana Alya Md Ghazali
Background: Obstructive sleep apnea (OSA) is sleep disorder characterized by repetitive partial or complete obstruction of the upper airway lasting for at least 10 seconds and is associated with hypoxia and daytime hypersomnolence. A surgical patient with undiagnosed OSA face potential detrimental effect from general anesthesia and certain perioperative medications. The gold standard for its diagnosis is by a polysomnography however it is expensive and not readily available in Malaysia. Therefore, patients may be evaluated with a STOP-Bang and an Epworth Sleepiness Scale (ESS) questionnaires to pick up patients at risk for OSA. Objective: To determine the prevalence of surgical patients at risk of OSA in preoperative anaesthesia clinic in Hospital Serdang. Methods: A cross-sectional study was conducted at the preoperative anaesthesia clinic in Hospital Serdang among the surgical population. All patients scheduled for surgery who meets the inclusion criteria were assessed according to their socio-demographic characteristics, anthropometric measurements as well as OSA symptoms by using the STOP-Bang questionnaire and the Epworth Sleepiness Scale (ESS). Data was analyzed by using IBM SPSS Statistics Version 21.0 for Windows. Results: The prevalence of high risk OSA patients was 38.6% among the surgical population with majority being Malay, male, aged more than 50 and hypertensive. The most reported symptom was tiredness or excessive daytime sleepiness. A significant association between risk of OSA and age group, gender, BMI, neck circumference and hypertension was obtained. Conclusion: Obstructive sleep apnea is a common sleep disorder which may pose danger to the surgical population when undiagnosed. Greater suspicions must be implied in surgical patients so that proper management can be carried out during the perioperative period. Keywords: Obstructive sleep apnea (OSA), Anaesthesia clinic, prevalence, surgical population, STOP-Bang questionnaire, Epworth Sleepiness Scale (ESS).